The appraisal of reproduction costs of historic properties: the case of Venetian Villas [La stima del costo di riproduzione delle dimore storiche: il caso delle Ville Venete] - Raul Berto; Antionio Prà; Sergio Pratali Maffei; Paolo Rosato (Valori e Valutazioni, 2022)
This paper illustrates a model for the quick estimate of the cost of reproduction of historic buildings, with particular regard to Venetian Villas. The goal is to provide an operational tool for the stipulation of an insurance contract, against partial or total damages, for products with an “accepted” value. This type of contract, although still not very widespread, allows, in the event of total destruction, to have the adequate resources for the reconstruction of the building in its original conditions, as far as possible. The “accepted value” insurance of the building becomes an instrument for the protection of the collective historical-architectural heritage. The article, in addition to illustrating the procedure in detail, presents a concrete application to historic homes in the Veneto region.